LEGAL STATUS OF INDIVIDUAL BANKRUPT DEBTORS AFTER TERMINATION OF BANKRUPTCY AND REHABILITATION UNDER INDONESIAN BANKRUPTCY LAW - Retnaningsih, Sonnyendah; Ikwansyah, Isis (Indonesia Law Review, 2017)
The Indonesian bankruptcy law system adheres to the debt collective principle which is general seizure (sita umum) of the debtor’s property as guarantee for the payment of debt through the bankruptcy institution. The principle of debt collective stresses that the debtor’s debt shall be paid immediately from the property owned by the debtor. Based on such principle, bankruptcy serves as a means of coercion to materialize the creditors’ rights through liquidation of the debtor’s assets. Bankruptcy law in Indonesia does not recognize the principle of debt forgiveness, among others, the implementation of debt relief granted to the debtor to pay off debts that are truly incapable of being fulfilled. According to the Bankruptcy Law, after the completion of the bankruptcy process, the debtor is no longer in a state of bankruptcy, because the end of bankruptcy has revoked the status of insolvent debtors, hence debtors are considered as being competent to take care of their property. However, the termination of bankruptcy does not necessarily absolve the debtor from the remainder of the debt; creditors are entitled to collect it and debtors are obligated to pay it off. Upon the completion of the bankruptcy process, debtors or their heirs may apply for rehabilitation. However, rehabilitation is only to be granted if all creditors state that they have obtained payment in a satisfactory manner, meaning that recognized creditors will not file claims against the debtor concerned again even though they may not have received payment on all of their outstanding receivables. Request for rehabilitation can only be granted if the debtor has completed the entire scheme of bankruptcy and creditors were satisfied with the payment.